Designing employees readiness to change intervention: does demographic differences on psychosocial predictors matters? - Mardhatillah, Amy Mardhatillah; Abdul Rahman, Shukran (2018)
The study aims to (1) examine demographic differences in term of employee readiness to change, namely; gender, age, job type, educational background and tenure in Higher Learning Institution (HLI). (2) identify differences on psychosocial predictors based on Holt (2007) theory across different demographic backgrounds. (3) and design employee readiness intervention based on demographic differences on psychosocial predictors of employees’ readiness to change. Method: 214 academics and 214 non-academic staff have been randomly sampled to participate in this study. T-test, One way ANOVA, and Multigroup moderation analysis were used to analyses the data. Two measures were used to examine variables namely; readiness to change scale by Durhan (1999) and psychosocial readiness to change by Holt (2007). Both scale are reliable with Critical Ratio value greater than 0.5.